Factors Influencing Intention To Use Tax E-Filing Systems: A Study On Taxpayers In West Malaysia - Mayeh, Moein (2013)
In recent years, Malaysian government has increasingly benefited from information technology to enhance their services, known as electronic government (e-government). However, despite considerable investment in e-government initiatives, citizens‟ adoption rate is still low. Tax e-filing system is one of the critical e-government services, which assist taxpayers in filing their tax returns electronically each year since 2006. Since citizens‟ acceptance of tax e-filing system plays an important role in the success of this system, there is a need to understand the factors that predict the users‟ intention to use tax e-filing system. This study, conducted a survey among taxpayers in Malaysia, aims to investigate the relationships between perceived security, perceived privacy, perceived service quality, e-trust, environmental friendliness, and facilitating conditions with the original constructs of combined Technology Acceptance Model-Theory of Planned behavior (Combined TAM-TPB). A total of 290 responses from five major states in Malaysia were analyzed in Smart PLS using Structural Equation Modeling (SEM). The results support all the hypotheses developed except the relationship between perceived usefulness and attitude. Attitude is also examined as a mediator for the relationships between environmental friendliness, e-trust, perceived usefulness and perceived ease of use with intention to use. Except for perceived usefulness and perceived ease of use, attitude is shown to be a mediator for all aforementioned relationships.